IMPLEMENTASI PENDEKATAN DISCOVERY LEARNING DENGAN METODE BIMBINGAN KELOMPOK PADA GURU SEKOLAH DASAR DI KECAMATAN PALAS - Laila Ratna (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The purpose of the study was to improve the implementation of Discovery Learning by the Group Guidance method for Elementary Teachers in Palas Subdistrict, South Lampung in 2018/2019 Academic Year. The research method uses School Action Research (PTS), with research flow within the 2004 National Education Department, the research cycle starts from planning (planing), organizing, observing and reflecting and following up. Data collection techniques were obtained through observation of activities, mentoring performance, implementation of Discovery Learning in learning, partnering with partners and colleagues. The results of Cycle I Counseling Performance reached a score of 44 (65%) Good category, Workability 19 (63%), Activity 18 (60%) Active. Cycle II Counseling Performance reached a score of 52 (76%) Good categories, Workability 21 (70%), Activity 23 (73%) Active. Cycle III Counseling Performance reached a score of 66 (97%) in the category of Very Good, Workability 26 or (87%), Activity 28 (93%) Active.